Environmentally friendly, antibacterial materials from recycled keratin incorporated electrospun PLA films with tunable properties - ERTEK, DİCLE AYÇA (My University, 2023)
© 2022 Elsevier LtdThe traditional disposal of chicken feathers includes expensive and challenging steps such as incineration and burying in landfills. Keratin is a valuable component of chicken feather waste recycled from poultry industry. The fibrous intermediate protein nature along with unique chemical composition enables its use in food, pharmaceutical, cosmetics and agricultural industries. The current study proposes an innovative valorization of recycled keratin from chicken feathers combined with polylactic acid (PLA), a viable bio-based polymer obtained from plant-based food stock. As a novel application, this study explains the preparation, electrospinning parameter optimization and performance assessment of recycled keratin electrospun with PLA. The structural, thermal, thermo-mechanical, morphological, antibacterial and surface wetting properties of keratin-incorporated electrospun PLA films were investigated. The disruption of crystallinity, hence the processability of both biopolymer via electrospinning is demonstrated. The nanofiber size, thermal, thermo-mechanical, antibacterial and surface wetting properties of electrospun films can be tuned by keratin content. This study provides environmentally friendly, recycled, bio-based material alternatives with tunable material properties that can be used in multitude of applications including environmental food packaging.
Keywords: Fizik; Astronomi ve Astrofizik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; Uzay bilimi; POLİMER BİLİMİ; KİMYA, ORGANİK; ASTRONOMİ VE ASTROFİZİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; SPACE SCIENCE; POLYMER SCIENCE; CHEMISTRY, ORGANIC; ASTRONOMY & ASTROPHYSICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Fizik ve Astronomi; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Physics and Astronomy; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; Antibacterial packaging; Keratin electrospinning; Poultry waste; Recycled keratin